PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI MOTIVASI DAN DISIPLIN DI LINGKUNGAN KERJA - Istiana; Muhtarom; Eri Purwanti; Dwi Rohmadi Mustofa (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2022)
Human resources that are kineja a person includes the mind and physical power that become animportant element in an organization. In other words, the success of an organization depends largelyon the performance of its employees, but in reality in schools employee performance is still relativelylow, this can be seen from the less effective working hours (not on time), and responsibility for tasksthat are still lacking. Therefore, the principal and researchers are trying to find out what most affectsthe motivation and discipline of employees, so that employee performance problems that often occurin the organization or institution in the school can be solved, if it can not be resolved at least thereis an improvement in performance. This study aims to find out the influence of improving humanresource performance through motivation and discipline in the work environment and to find outwhether there are inhibitory factors and support the improvement of human resource performancethrough motivation and discipline in the work environment. Respondents in this study were selectedusing the proposiv sample method by distributing questionnaires to as many as 53 employees. It canbe explained that the influence is caused by the work environment, discipline and work motivation.There is a significant positive influence of the work environment, discipline, and work motivationtogether on the performance of Human Resources.